Radiocesium concentrations in mushrooms collected in Kawauchi Village five to eight years after the Fukushima Daiichi Nuclear Power Plant accident - Cui, Limeng; Orita, Makiko; Taira, Yasuyuki; Takamura, Noboru (PloS one, 2020)
Following the Fukushima Daiichi Nuclear Power Plant accident in March 2011, radionuclides such as iodine-131, cesium-134 and cesium-137 were released into environment. In this study, we collected wild mushrooms from the Kawauchi Village of Fukushima Prefecture, located less than 30 km southwest of the Fukushima nuclear power plant, to evaluate their radiocesium (134Cs+137Cs) concentrations and the risk of internal radiation exposure in local residents. 342 mushroom samples were collected from 2016 to 2019. All samples were analysed for radiocesium content by a high-purity germanium detector. Among 342 mushroom samples, 260 mushroom samples (76%) were detected the radiocesium exceeding the regulatory limit of radiocesium (100 Bq/kg for general foods in Japan). The median of committed effective dose from ingestion of wild mushrooms was in the range of 0.015-0.053 mSv in 2016, 0.0025-0.0087 mSv in 2017, 0.029-0.110 mSv in 2018 and 0.011-0.036 mSv in 2019 based on the assumption that Japanese citizens consumed wild mushrooms for 1 year. Thus, our study showed that although radiocesium is still detected in mushrooms collected in Kawauchi village even after 5 to 9 years later, the committed effective dose due to consuming mushrooms was lower than 1 mSv per year. Long-term comprehensive follow-up should monitor radiocesium concentrations in wild mushrooms to support the recovery of the community after the nuclear disaster.